1994
DOI: 10.1111/j.1365-2958.1994.tb00344.x
|View full text |Cite
|
Sign up to set email alerts
|

mRNAs in the methanogenic archaeon Methanococcus vannielii: numbers, half‐lives and processing

Abstract: Cells from the early exponential growth phase of cultures of the methanogenic archaeon Methanococcus vannielii have been shown to contain c. 180 transcripts of the mcrBDCGA (mcr) operon, c. 100 transcripts of the MvaL1,L10,L12 (Mva) operon, c. 8 transcripts of the argG gene and c. 1 transcript of the secY gene. These values decreased to c. 50 mcr transcripts, c. 30 Mva transcripts, c. 3 argG transcripts and < 1 secY transcript per cell as the cultures entered the stationary phase of growth. Addition of bromo-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 68 publications
1
34
1
Order By: Relevance
“…Transcription of the genes that encode MRI (the mcr operon) and MRII (designated the mrt operon, for methyl reductase two [31,32]) might therefore be differentially regulated by growth conditions in M. thermoautotrophicum strains. This is in contrast to the results recently reported for Methanococcus vannielii, which apparently contains only one MR-encoding region, which is transcribed under all growth conditions (14). To address this directly, the sequences of both the mcr and mrt operons were needed from the same M. thermoautotrophicum strain to identify sequences that could be used as transcript-specific probes.…”
contrasting
confidence: 54%
“…Transcription of the genes that encode MRI (the mcr operon) and MRII (designated the mrt operon, for methyl reductase two [31,32]) might therefore be differentially regulated by growth conditions in M. thermoautotrophicum strains. This is in contrast to the results recently reported for Methanococcus vannielii, which apparently contains only one MR-encoding region, which is transcribed under all growth conditions (14). To address this directly, the sequences of both the mcr and mrt operons were needed from the same M. thermoautotrophicum strain to identify sequences that could be used as transcript-specific probes.…”
contrasting
confidence: 54%
“…2, mtaA1, mtaC1 plus mtaB1, and pta plus ackA constituted three separate operons. Next, using RT-qPCR, the in vivo halflives of mtaA1, mtaC1B1, and pta-ackA transcripts were determined in the 30°C and 15°C cultures after inhibiting transcription with 100 g/ml actinomycin D according to the method of Hennigan and Reeve (30). The results showed that mtaA1 and mtaC1B1 were very stable in the cultures grown at both temperatures, with half-lives of about 1 h. In contrast, the half-life of ptaackA was relatively short (25 min) at 30°C and even shorter (15.5 min) at 15°C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Degenerate oligonucleotide probes were constructed with the N-terminal sequences of both subunits of the 480-kDa CoM methylase (55) RNA isolation and Northern hybridizations. RNA was prepared and Northern blotting was performed by modifications of the techniques described by Hennigan and Reeve (27) and Pihl et al (45). M. barkeri was grown to the mid-log phase and harvested by filtering through Whatman no.…”
Section: Methodsmentioning
confidence: 99%